ALT-803 in the treatment of non-muscle-invasive bladder cancer: Preclinical and clinical evidence and translational potential - Chen, Wujun; Liu, Ning; Yuan, Yang; Zhu, Meng; Hu, Xiaokun; Hu, Wenchao; Wang, Shuai; Wang, Chao; Huang, Binghuan; Xing, Dongming (Frontiers in Immunology, 2022)
Bladder cancer (BCa) is one of the most common malignant tumors that cause death. Approximately 75%–85% of BCa develop into non-muscle-invasive bladder cancer (NMIBC). Bacillus Calmette-Guérin (BCG) is the gold standard for avoiding cystectomy in the treatment of NMIBC. Unfortunately, up to 30% of patients do not respond to BCG treatment, and up to 70% of BCG responders relapse. The United States Food and Drug Administration (FDA) approved valrubicin (1998) and pembrolizumab (2020) for the treatment of BCG-unresponsive (BCGu) NMBIC. However, the complete remission rate for valrubicin and pembrolizumab was only 16% and 40.6%, respectively. ALT-803 (N-803) is an IL-15 superagonist and reduces tumor burden by promoting the proliferation and activation of NK cells and CD8+ T cells. The FDA received (23 May 2022) and accepted to review (28 July 2022) the marketing submission of ALT-803 plus BCG for the treatment of BCGu NMIBC. However, the FDA previously rejected the application for oportuzumab monatox (OM) due to a lack of data comparing it with pembrolizumab on August 20, 2021. Interestingly, the clinical efficacy and safety of ALT-803 were higher than that of pembrolizumab and OM, suggesting that ALT-803 may be approved by FDA. This review aims to further knowledge of the preclinical and clinical evidence of ALT-803 in the treatment of NMIBC and discuss its translational potential.